The thermoregulator the of retina: The choroid [Retinanin termoregülatórü: Koroid] - (:unkn) unknown (Gazi Eye Foundation, 2014)
The retina is a sensitive layer of the eye that is exposed to harmful effects of light. Besides nourishing the outer layers of the retina, the choroid tissue has additional functions such as scleral growth, emmetropisation and the vasomotor control of intraocular pressure. One of the vital but mostly disregarded functions of the choroid is the prevention of retinal damage. This article discusses the retinal damage prevention mechanisms and the retinal thermoregulatory function of the choroid as well as the development of main pathologies such as age-related macular degeneration with choroidal dysfunction.
Keywords: Age-related macula degeneration; Choroid; Retina; Solar retinopathy; Thermoregulation